Vocational Pre-Teacher Students' Perceptions on Online Learning During Covid-19 Pandemic in Java, Indonesia: Benefits, Challenges, and Suggestions - Towip Towip; Yuyun Estriyanto; Ngatou Rohman; Suharno Suharno; Nugroho Agung Pambudi (Universitas Sebelas Maret, 2020)
Online learning has increased rapidly in Indonesia's higher education since the government enforced to combat the spread of COVID-19. However, inequality in implementation has become an issue in several countries. In Indonesia, with archipelagic and mountainous topography has several challenges. Therefore, the present study is aimed to evaluate and analyze the benefits, challenges, and suggestions of online learning in Indonesia for future improvement. A total of 271 students were surveyed and provided complete information regarding the survey. Quantitatively, the instrument of the survey data is analyzed by using SPSS software. Qualitatively, data from open-ended participants' responses were analyzed by qualitative content analysis to explore the findings from the survey. The result showed that online learning was more efficient, provided easy communication, improve students' engagement, and developed their virtual learning skills. However, it was also found that the overall students were still unsatisfied since the uneven infrastructures of internet connectivity and learning arrangements not good enough. In line with this, media, processes, facilitators skills, and assessments needed further improvement. Students’ suggestions for improving online learning quality are discussed as well.